The theology of Abu l-Qasim al-Balkhi/al-Ka'bi (d. 319/931) - Omari, Racha Moujir el. (Islamic Philosophy, Theology and Science. Texts and Studies, 2016)
This is the first comprehensive monograph on the theology of Abū l-Qāsim al-Kaʿbī al-Balkhī (d. 319/931), a leading Muʿtazilī who flourished at the end of the Baghdādī school and at the beginning of the scholastic phase of Muʿtazilī history. The study of al-Kaʿbī's theology has been hindered by historiographical barriers: the fragmentary nature of extant articles, and the difficulties of reconstructing their contexts. This work investigates the twofold challenge of recovering al-Kaʿbī's theology on the basis of a source-critical reconstruction of major extant fragments. One result of this study positions al-Kaʿbī's theology as influenced less by the precepts of a Baghdādī school, and guided more by his individual views and affinity for earlier independent Muʿtazilī positions. Another result not only corroborates al-Kaʿbī's previously noted contributions in epistemology and cosmology, but also argues for their centrality to his theology as a whole.